Chapter 5: Kaitiakitanga: Land, People and Resource Management - Kawharu, Merata (Te kōparapara: an introduction to the Māori world, 2018)
Keywords: environment; history; kaitiakitanga; resource management; social conditions; social life and customs

The Foreshore and Seabed Act: Five years on, where to from here - Whare, Tracey (Māori and the environment: kaitiaki, 2010)
Keywords: citizenship; environment; environmental policy; kaitiakitanga; print only; social life and customs; taiao; water management

Chapter 10: Feast or Famine: Customary Fisheries Management in a Contemporary Tribal Society - Tuuta, Evelyn (Waitangi Revisited, 2005)
Keywords: crown policy; environment; government relations; history; kaitiakitanga; land tenure; māori rights; race relations; rangatiratanga; resource management; tiriti o waitangi/treaty of waitangi

Māori Urban Protest Movements - Taonui, Rawiri (Huia histories of Māori: ngā Tāhuhu Kōrero, 2012)
"Collection of 17 essays from Māori scholars which cover customary law, ancestral law, the natural world, Māori urban protest, health, politics, and customary language and expression"--Publisher's information.
Keywords: discrimination; foreshore and seabed act 2004; government relations; hikoi ki waitangi; history; kaitiakitanga; land march; māori womens welfare league; nga tamatoa; parihaka; poverty; protest; racism; rangatiratanga; resistance; social conditions; springbok tour protests; takaparawhau bastion point; tikanga | indigenous law; tiriti o waitangi/treaty of waitangi; tāngata whenua; urbanisation

Māori Interests and Rights: Four Sites at the Frontier - Bargh, Maria; Jones, Carwyn (Public Policy and Governance Frontiers in New Zealand, 2020)
Keywords: crown policy; government; iwi politics; kaitiakitanga; kāwanatanga; māori rights; rangatiratanga